2021
DOI: 10.3390/agronomy11061186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Tunnel Microclimate on Fruit Quality and Calcium Concentration in ‘Santina’ Sweet Cherries in a Mediterranean Climate

Abstract: The use of protective covers, such as high tunnels, is recognized as an effective technology to reduce rain-induced fruit cracking in sweet cherries; however, there is a lack of information concerning the effects of this production system on the fruit’s mineral concentration, quality, and postharvest life. This study assesses the feasibility of using high tunnels on ‘Santina’ sweet cherries under the Mediterranean climate of the Central Valley of Chile to obtain earlier harvests of high-quality fruit with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…In this work, in order to assess the impact of light exposure on fruit quality, fruits of the upper and lower area of the canopy were evaluated separately. As a result, we detected firmer fruits in the lower area of the canopy, independent of the treatments, which had already been observed in previous studies in a temperate climate [21,25]; this could be in response to a delay in the maturation of fruits located in the lower area of the canopy, which is highly shaded by the upper area. Reduced sweet cherry fruit firmness by the use of plastic covers detected here, which has also been previously reported [18,21,22], could be explained by the lower levels of calcium (Ca) detected in fruits grown under plastic covers [25].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this work, in order to assess the impact of light exposure on fruit quality, fruits of the upper and lower area of the canopy were evaluated separately. As a result, we detected firmer fruits in the lower area of the canopy, independent of the treatments, which had already been observed in previous studies in a temperate climate [21,25]; this could be in response to a delay in the maturation of fruits located in the lower area of the canopy, which is highly shaded by the upper area. Reduced sweet cherry fruit firmness by the use of plastic covers detected here, which has also been previously reported [18,21,22], could be explained by the lower levels of calcium (Ca) detected in fruits grown under plastic covers [25].…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, the cultivation of sweet cherry in the southern zone (temperate rainy climate) is frequently affected by several climatic constraints, including the high incidence of rains at bloom and pre-harvest, which forces producers to use plastic covers to mitigate flower falls and, most importantly, fruit cracking. The impact of the use of plastic covers on sweet cherry has been poorly explored; however, some studies have shown that its use can increase the caliber and reduce the cracking [41,42] of fruits but decrease cherry firmness [18,21,22,25] and soluble solids contents [43,44]. On the other hand, according to information provided by the fruit export company Ranco Cherries of Chile, the cherry produced in southern Chile exhibits low acidity levels, which worsens with the use of covers, a factor that is stronger in more southern regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations